Psychological Health and Spiritual and Moral Values of Young People of Conscription age in the Context of the Destructive Information and Psychological Influence - A.B. Serykh; L.F. Buksha; E.V. Osipova; E.N. Nazarskaya (Клиническая и специальная психология)
The work is aimed at studying the psychological health and spiritual and moral values of young people of conscription age in the context of the destructive information and psychological influence. The results of an empirical study conducted in 2024 on the territory of 4 regions of the Russian Federation are presented: Arkhangelsk, Kaliningrad, Leningrad and Murmansk regions. The total number of respondents was 1,050 young people of draft age aged 16 to 20 years. The following were used in the study: the author's questionnaire “Information and psychological impact”; the questionnaire “Motivational structure of information activity”; the questionnaire “Spiritual personality”; the methodology “Individual model of psychological health”. The obtained results allow us to say that, on average, young people of conscription age often encounter content in the Internet space that has a destructive informational and psychological impact, while they have a fairly high degree of trust in this content. It is noted that young people exposed to destructive information may experience social isolation, mistrust and aggression, which prevents them from forming healthy social connections, leads to a decrease in psychological health and has a destructive effect on internal values and spiritual and moral guidelines. In such conditions, a more pessimistic perception of the world is formed, which undermines the basic principles of spirituality and morality, in particular, such as sincerity, politeness and the pursuit of truth.